KEPUTUSAN INVESTASI PEMILIK MODAL HOTEL BERBINTANG (Studi Kasus pada PT.”X” Pemilik Hotel “Y” Jember) - Yuwono, Chandra Setiawan Tri (Universitas Muhammadiyah Jember, 2016)
Based on the growth rate of the hotel that indicated the level actual disbursement of credit showed a positive increase. The compositional in the Gross Regional Domestic Product (GRDP) shows an arrangement of the hotel GRDP lower?than the Wholesale & Retail GRDP, as well as the Restaurant GRDP. The occupancy rate of tourists, both foreign and domestic showed a significant decrease each year. With that data PT.